The Analysis of Curriculum Approaches in Foreign Language in Indonesia - Noor Muthiah; Hesty Widiastuty; Mardalius (Jurnal Ilmu Pendidikan Nasional (JIPNAS), 2024)
Foreign language education in Indonesia is evolving with the progress of globalization and increasing exchanges between countries. One of the key aspects of foreign language teaching is the curriculum approach used in the learning process. The purpose of this article is to analyze the curriculum approach used in foreign language teaching in Indonesia. This approach encompasses a variety of curriculum design methods and strategies and focuses on key aspects of foreign language learning. The purpose of this article is to examine curricular approaches to foreign language teaching in Indonesia. This type of research is qualitative research (qualitative research). Qualitative research seeks to understand and interpret the meaning of events in specific situations from the researcher's unique perspective. Qualitative research is a research-based process for understanding the problems of understanding and interpreting texts and creating big pictures from words in a scientific setting. The data collection method used in this study is a data collection method using the library search method. The results of this study demonstrate that this approach has been used as a perspective for curriculum development. Each institution takes a different approach depending on the educational goals they are trying to achieve.